A Power Paradox: Growth of the Hydro Sector in Nepal - Shrestha, Ratna Sansar; Biggs, Stephen; Justice, Scott; Gurung, Amanda Manandhar (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
Nepal has tremendous hydropower potential yet paradoxically experiences, until recently, loadshedding of up to 18 hours daily in the dry season and has not achieved self-reliant energy security. This paper analyses this paradox by reviewing the growth of hydroelectricity sector in Nepal. It identifies four phases; the illustration of technical capacity, industrial training and early investments, major policy challenges and paradigm shift and maturing hydropower sector. The spread of improved water mills as well as hydro installations is also reviewed briefly. The paper argues that Nepal will meet much of its projected national demand very soon (2018/19) but attaining self-reliant energy security after displacing fossil fuel is not in the horizon yet. While substantial hydro investments are in the pipeline; a strong, diverse hydro-mechanical manufacturing industry is established. But the electro-mechanical industry is non-existent. Policies have attracted substantial private investment in hydropower sector, but it is not geared towards the use of electricity for overall economic development of Nepal and has yet to streamline policy with respect to lean season augmented flow of water for drinking and irrigation purposes within and outside Nepal. A more fundamental paradox is that Nepal government has yet to acknowledge these anomalies that hinder sustainable economic developments. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 23 Year: 2018